Performance of The Election Supervisory Agency in The Implementation of The 2020 Surakarta City Election - Doris Rahmat; Aris Tri Haryanto; Adi Purwanta (East Asian Journal of Multidisciplinary Research, 2022)
This research departs from the indications of violations found in regional head elections, such as campaigns that are not in accordance with the rules of the General Election Commission (KPU) and the State Civil Apparatus (ASN) who favor one pair of candidates and vote counting, illegal voter registration, intimidation against voters who are contrary to the spirit of the Election Law or not in accordance with democratic principles. In this case, the performance of the Election Supervisory Body (Bawaslu) of Surakarta City in carrying out its duties and authorities. This research is descriptive with a qualitative approach, namely the researcher tries to describe and reveal all phenomena, symptoms, events as they are in the form of descriptions. The prevention carried out by Bawaslu also involves the general public in the form of participatory supervision. However, if there is a violation during the campaign, Bawaslu can only reprimand it. Because the rules in the General Election Commission Regulation (PKPU) regarding prohibitions that must be avoided. Law Number 32 of 2004 which states that regional heads and deputy regional heads are elected in one pair of candidates which is carried out democratically based on the principles of direct, general, free, confidential, honest and fair.